An advanced frequent closed sequences using BIDE - Vineela, K; V.B.T. Santhi, M; V.V. Gowtham Srujan, N; Ashok, V (International Journal of Engineering and Technology, 2018)
According to the past reasearches which produced few argumented stating that the frequent mining algorithm should only be closed but not frequent, as it not only results in compact but also complete results, and also in greater effectiveness. Most of the previous algorithms have mainly provided a direct test strategy to detect. In this article, we provide an Advanced BIDE, which is an effective algorithm used for processing query methods frequently closed. BI-Directional extension algorithm is better in pruning or filtering the search space when compared to any other algorithm. It is related to the calculation of frequent samples of search engines by parent-child relationships. An experimental study based on a variety of real historical data demonstrates the effectiveness and measurability of A-BIDE on the known alternatives of the past. It can also be scaled in terms of size of a query. Â